2021
DOI: 10.1021/acs.jpcc.1c06784
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of IR Spectroscopy of Adsorbed CO for the Characterization of Heterogeneous Catalysts Containing Isolated Atoms

Abstract: This Perspective discusses the characterization by infrared spectroscopy of CO adsorbed of isolated metal atoms, also referred to as single atom catalysts (SAC). The main difficulties encountered during the analysis are briefly discussed, e.g., band assignment, sample structural evolution, spectral corrections, and signal enhancement. Theoretical investigations by DFT stressed the high number of surface structures that may be considered for the support (e.g., crystal termination, partial reduction or not) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 64 publications
7
51
2
Order By: Relevance
“…As shown in Figure , all samples only showed a peak located around 2090 cm –1 , which we assign to CO adsorbed on isolated Pt 2+ cations (i.e., Pt single atoms). ,, We recognize that other authors have reported CO-IR bands assigned to CO-Pt isolated species in Pt/ceria, ranging from 2088 to 2095 cm –1 . It has also been suggested that definitive assignment of the adsorbed CO band can only be performed with samples that have very low Pt loading (0.05 wt %) since higher loadings can lead to the formation of sub-nanometer clusters . Meunier has described the challenges in unambiguously assigning IR bands. We note that our assignment of the band in Figure is based not just on the peak position but the physical characteristics of the CO band as well.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…As shown in Figure , all samples only showed a peak located around 2090 cm –1 , which we assign to CO adsorbed on isolated Pt 2+ cations (i.e., Pt single atoms). ,, We recognize that other authors have reported CO-IR bands assigned to CO-Pt isolated species in Pt/ceria, ranging from 2088 to 2095 cm –1 . It has also been suggested that definitive assignment of the adsorbed CO band can only be performed with samples that have very low Pt loading (0.05 wt %) since higher loadings can lead to the formation of sub-nanometer clusters . Meunier has described the challenges in unambiguously assigning IR bands. We note that our assignment of the band in Figure is based not just on the peak position but the physical characteristics of the CO band as well.…”
Section: Resultssupporting
confidence: 57%
“…20−23 It has also been suggested that definitive assignment of the adsorbed CO band can only be performed with samples that have very low Pt loading (0.05 wt %) since higher loadings can lead to the formation of sub-nanometer clusters. 24 Meunier 25 has described the challenges in unambiguously assigning IR bands. We note that our assignment of the band in Figure 8 is based not just on the peak position but the physical characteristics of the CO band as well.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…This difference is significant, but not as large as in a previously reported study, where FWHM was ~10, 25, and 40 cm −1 for CO adsorbed on metallic Pt [41]. The broadening of CO adsorption peak is presumably attributable to inhomogeneity of adsorption sites and can be related to different sizes of metallic particles [42].…”
Section: Co-driftscontrasting
confidence: 49%
“…This band may be assigned to CO adsorbed on partially oxidized Pt. Several authors have proposed that CO could bound strongly to PtOx species and be unreactive [9,27,38], although the exact nature of the sites, e.g., single Pt cation or PtOx clusters, is still debated, as discussed in a recent review [31]. The main linear CO band on the Pt/alumina sample can thus be assigned to two different Pt species, one oxidized (2085 cm −1 ) and one reduced (ca.…”
Section: Resultsmentioning
confidence: 99%
“…The samples used here exhibits a more complex IR signal than those reported in previous studies [6,30], indicating the presence of various metallic and cationic Pt species. It must be stressed that the present study did not aim at determining the exact nature of the bands observed, particularly those located around 2090 cm −1 on Pt/CeO 2 , the assignment of which is still controversial [31]. The effect of the presence of molecular oxygen will also be assessed.…”
Section: Introductionmentioning
confidence: 94%